Controls on subsurface methane fluxes and shallow gas formation in Baltic Sea sediment (Aarhus Bay, Denmark). (1st September 2016) - Flury, Sabine; Røy, Hans; Dale, Andrew W.; Fossing, Henrik; Tóth, Zsuzsanna; Spiess, Volkhard; Jensen, Jørn Bo; Jørgensen, Bo Barker
Abstract: Shallow gas accumulates in coastal marine sediments when the burial rate of reactive organic matter beneath the sulfate zone is sufficiently high and the methanogenic zone is sufficiently deep. We investigated the controls on methane production and free methane gas accumulation along a 400 m seismo-acoustic transect across a sharp transition from gas-free into gas-bearing sediment in Aarhus Bay (Denmark). Twelve gravity cores were taken, in which the pore water was analyzed for inorganic solutes while rates of organic carbon mineralization were measured experimentally by 35 SO4 2− radiotracer method. The thickness of organic-rich Holocene mud increased from 5 to 10 m along the transect concomitant with a shallowing of the depth of the sulfate-methane transition from >4 m to 2.5 m. In spite of drastic differences in the distribution of methane and sulfate in the sediment along the transect, there were only small differences in total mineralization, and methanogenesis was only equivalent to about 1% of sulfate reduction. Shallow gas appeared where the mud thickness exceeded 8–9 m. Rates of methanogenesis increased along the transect as did the upward diffusive flux of methane. Interestingly, the increase in the sedimentation rate and Holocene mud thickness had only a modest direct effect on methanogenesis rates in deep sediments. This increase in methane flux, however, triggered a shallowing of the sulfate-methane transition which resulted in a large increase in methanogenesis at the top of the methanogenic zone. Thus, our results demonstrate a positive feedback mechanism that causes a strong enhancement of methanogenesis and explains the apparently abrupt appearance of gas when a threshold thickness of organic-rich mud is exceeded.